Exploring linked in behaviour of librarians and information professionals in Nigeria (2018)
Professional networking is a way of interacting with colleagues in the same field and the emergence of Internet technology’, had made it easy and faster. This paper used Theory of Reasoned Action (TRA) to investigate the use of Linkedln among librarians and information professionals in Nigeria. The study adopted survey approach, online questionnaire for data collection, and 125 librarians and information professionals responded to the survey. Hypothetically, relationship among attitude, subjective norms, intention to use and use were examined. Descriptive statistics were used to analyse research questions while Pearson Product Moment Correlation was used for the hypotheses. The results revealed that both 'attitude' and 'subjective norm' had positive association with 'intention' however, 'attitude' had a stronger positive association than 'subjective norm'. In addttion, the finding validated TRA model as it found that 'intention' had a very strong positive association on 'behaviour'. The findings indicate that attitude is a critical antecedent to intention to use Linkedln, besides; subjective norm has influence on intention to use Linkedln. It implies that right attitude to use of Linkedln by Librarians and Information Professionals (LIPs) and positive influence of colleagues on one another will be an effective way of encouraging use of Linkedln among LIPs in Nigeria and its adopt ion for library services